Laboratory training manual on the use of isotopes and radiation in soil-plant relations research: a joint undertaking by the IAEA and the Food and Agriculture Organization of the United Nations - 7924 International Atomic Energy Agency; Food and Agriculture Organization of the United Nations (Vienna : [s.n], 1964)
36